Eorpeburnan and Rye: some aspects of late Anglo-Saxon settlement development in East Sussex. (2nd July 2020) - Haslam, Jeremy
ABSTRACT: Reasons are given for questioning the identification of the defended site of Castle Toll in Kent with the late ninth-century Burghal Hidage burh of Eorpeburnan, in eastern Sussex, as has been widely assumed. A new historical narrative is therefore required. A consideration of the relevant topographical, landscape, archaeological, and documentary evidence supports the case for identifying the burh of Eorpeburnan with Rye, East Sussex. Recent palaeogeographic and geomorphological evidence relating to the development of the Romney Marsh area gives a new perspective to this hypothesis, and a new context for the development of Rye in the historic landscape. Some aspects of the historical relationship of Rye with Hastings and with Old Winchelsea are also explored.